CEO’s characteristics and firms’ specific factors on optimal leverage in Malaysia - Shafie, Shazlin; Ab Razak, Nazrul Hisyam; Chua, Mei Shan; Lau, Wei Theng (Academic Inspired Network, 2020)
This study conducted to investigate the CEO’s characteristics and firms’ specific factors on optimal leverage in Malaysia by employing 472 observations and 50 listed companies (non-financial firms) for 11 years period, 2008-2018. This study pays attention to the dynamic aspect of capital structure which is a relatively new area in the finance literature. The objective of this study is to investigate managerial (CEOs) characteristics and firm’s factors in optimal leverage by applying dynamic model consistent with dynamic capital structure nature. By employing dynamic panel data, this study analyses the data through twostep system GMM introduced by Blundell & Bond (1998) consistent with past empirical studies. This finding shows that CEOs characteristics and the firm’s specific factors significantly impact optimal leverage in Malaysia’ companies. Hence, we accept alternate hypotheses in this study. This study would contribute to actual practise on identifying determinants of optimal leverage in proper forecasting and take action on controlling/managing all the significant variables to meet the optimal leverage in their practice. Meanwhile, the future researcher will gain more understanding of dynamic model and allow them to apply this finding as a comparison with their future study by supporting their literature review.